DETERMINATION OF ROCK MASS DEFORMATION MODULUS BASED ON GEOTECHNICAL AND GEOPHYSICAL SURVEYS: SAMARINDA TUNNEL CASE STUDY - Octavia Jawak, Efa
Samarinda is one of the biggest cities in East Kalimantan province and one of economy center and government in Indonesia. High traffic mobility reguires a plan to build 400 meters tunnel to maintain the smooth flow of traffic in that area. In the construction of a tunnel, the deformation modulus is one of the important parameters needed to create a numerical model for various rock engineering projects. Laboratory tests are often inadeguate to accurately determine the deformation modulus of the rock mass, so an empirical approach and in situ tests are used. Based on the geological survey, the resesearch location was dominated by soil, high weather claystone, medium weather claystone and sandstone with dominant rock mass guality in RMR class II ,III and IV. Based on laboratory test, it was obtained that the average of modulus elasticity is 510 MPa, 1805 Mpa and 470 MPa for Claystone, Sandstone and Siltstone materials. From pressure meter test (PMT) measurements, the range of deformation modulus is 12 MPa until 915 MPa. And from seismic downhole the range of deformation modulus is 39 MPa until 14,756 MPa. On the other side, from seismic downhole measurements found that the shear wave velocity (Vs) for the research location more than 750 m/s, which means that the research location is classified as a rock class site according to SNI 1726:2019 (Classification of rock class sites). Deformation modulus based on laboratory tests, pressure meter tests (PMT), seismic downhole and empirical approaches, correlations were made with Rock Mass Rating (RMR). From the correlation results, the strongest correlation was obtained between deformation modulus of the pressure meter test (PMT) and the RMR. A new eguations obtained from the relationship between PMT and RMR are Epm1-2.8562e0-0661RMR with R2—0.65. This eguation can be used for the Medium Weather Claystone and Sandstone materials at bore holes point along the tunnel and it's can be used as a consideration in the Samarinda tunnel design.